Hubungan Pemeriksaan Basil Tahan Asam pada Penderita Tuberkulosis Sebelum dan Sesudah Pengobatan Rifampicin Selama 6 Bulan di Rumah Sakit Tingkat III 04.06.01 Wijaya Kusuma Purwokerto - Cici Farhana Ambarwanty Mohtar; Epsi Marwati; Delita Septining Tyas (Universitas Muhamadiyah Manado, 2021)
Tuberculosis is a lung infection caused by the bacteria Mycobacterium tuberculosis. Early detection is one of the ways to detect tuberculosis. The first detection of tuberculosis is with the Molecular Rapid Test, which is one of the technologies being developed using GeneXpert. Patients with positive Molecular Rapid Test results will be treated with rifampicin for 6 months, then further screening of Acid-Fast Bacilli microscopically will be carried out to determine whether the patient is still positive for pulmonary tuberculosis or not. The purpose of this study was to determine the relationship between acid-fast bacillus examination in tuberculosis patients with positive molecular rapid test results. This study will be conducted experimentally. The results of calculations using the Wilcoxon Test showed that there was a relationship between TCM examination results and BTA follow-up screening in TB patients after and before rifampicin treatment for 6 months.